Influencing COX-2 Activity by COX Related Pathways in Inflammation and Cancer - Yu, Tingting; Lao, Xingzhen; Zheng, Heng (Mini Reviews in Medicinal Chemistry, 2016)
Cancer is a major cause of death worldwide despite significant advances in surgery and biology. Several recent studies have suggested that there is a close connection between tumorigenesis and inflammation. Cyclooxygenase-2 (COX-2), a link between inflammation and cancer, was proposed as a prime target for cancer therapy. However, the main available COX-2 inhibitors, nonsteroidal antiinflammatory drugs (NSAIDs), have several side effects that limit their application in cancer treatment. Additional research is needed to identify drugs that can regulate COX-2 or prostaglandin E2 (PGE2) with greater efficacy. Understanding the mechanism of COX-2/PGE2-mediated cancer and inflammation would be very useful for successful drug development. Progress of research and development into the role of COX related signaling both in inflammation and tumorigenesis in recent years has been summarized and introduced in this paper. Novel drugs designed to inhibit COX-2-related cancers are discussed to provide references for further development of novel drugs.
Keywords: Cancer